Phospholipase PLA2G16 Accelerates the Host Interferon Signaling Pathway Response to FMDV - Bingjie Sun; Xiaodong Qin; Taoqing Zhang; Sujie Dong; Yinbo Ye; Changying Wang; Yan Zhang; Rongzeng Hao; Yi Ru; Hong Tian; Haixue Zheng (Viruses)
PLA2G16 is a member of the phospholipase A2 family that catalyzes the generation of lysophosphatidic acids (LPAs) and free fatty acids (FFAs) from phosphatidic acid. Previously, PLA2G16 was found to be a host factor for picornaviruses. Here, we discovered that the Foot-and-Mouth Disease Virus (FMDV) infection led to an elevation in PLA2G16 transcription. We established PLA2G16 overexpression and knockdown cell lines in PK-15 cells to investigate the potential role of PLA2G16 in FMDV infection. Our findings revealed that during FMDV infection, PLA2G16-overexpressing cells had increased levels of phosphorylated STAT1 and the interferon-stimulating factors ISG15 and ISG56. In PLA2G16-overexpressing cells, p-STAT1 was observed at higher levels and earlier than in wild-type cells. Subsequent research demonstrated that PLA2G16 specifically promoted an antiviral innate immune response against FMDV. The host could detect the early release of FMDV viral nucleic acid in PLA2G16-overexpressing cells and trigger the interferon signaling pathway. Additionally, we discovered that the supernatants of PLA2G16-overexpressing cells stimulated the production of higher levels of ISG56 and phosphorylated STAT1. This suggests that PLA2G16-overexpressing cells can activate the innate immune pathway of uninfected cells after FMDV infection.